1977
DOI: 10.2320/matertrans1960.18.155
|View full text |Cite
|
Sign up to set email alerts
|

A Calorimetric Study of the Phase Transformation in Tantalum Hydrides

Abstract: On the basis of these results, a revised phase diagram is presented. The transformation entropy is well accounted for by the configurational entropy change of the hydrogen atoms evaluated from the structure models proposed here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Tantalum, a group 5 element, is of fundamental interest due to its superconducting properties, and many aspects of tantalum and its compounds have been studied in depth. , In recent decades, several stoichiometries of tantalum hydrides have been investigated at ambient pressure. Asano et al reported that tantalum hydrides form an interstitial solid solution of hydrogen in tantalum over a wide composition range, and nine phases of Ta–H compounds were reported by Schober et al Simonović et al synthesized tantalum hydrides of various compositions by equilibrating tantalum with hydrogen in the temperature range 573–823 K under a constant hydrogen pressure of 1 bar . Near Ta 2 H, hydrogen ordering occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Tantalum, a group 5 element, is of fundamental interest due to its superconducting properties, and many aspects of tantalum and its compounds have been studied in depth. , In recent decades, several stoichiometries of tantalum hydrides have been investigated at ambient pressure. Asano et al reported that tantalum hydrides form an interstitial solid solution of hydrogen in tantalum over a wide composition range, and nine phases of Ta–H compounds were reported by Schober et al Simonović et al synthesized tantalum hydrides of various compositions by equilibrating tantalum with hydrogen in the temperature range 573–823 K under a constant hydrogen pressure of 1 bar . Near Ta 2 H, hydrogen ordering occurs.…”
Section: Introductionmentioning
confidence: 99%
“…[6] In the Ta-H system, the ordered b-Ta 2 H phase exists around H/Ta = 0.5 at room temperature. [23,28] Thus, we can propose that when the temperature reaches the ordering temperature during cooling, multiple cracks such as concentric-and microcracks are introduced in Ta, finally giving rise to flaky debris and powders. In other words, the hydrogen-induced cracking and pulverization are due to the ordered b-Ta 2 H formation.…”
Section: Discussionmentioning
confidence: 99%